(untitled) (Iranian Journal of Kidney Diseases, 2019)
Introduction. Chronic kidney disease (CKD) promotes hypertrophy and fibrosis in heart, and increases the risk of cardiovascular mortality. Ferric citrate is a dietary phosphate binder used to control hyperphosphatemia in CKD patients. It has been shown to raise iron stores, improve anemia and secondary hyperparathyroidism, and decrease vascular calcification in CKD patients. The present study was done to explore the effects and mechanism of actions of ferric citrate on cardiac hypertrophy and fibrosis. Materials and Methods. Male SD rats were randomized to CKD (5/6 nephrectomized) and sham-operated control groups. CKD rats were fed regular diet or a diet containing 4% ferric citrate. After 8 weeks, hemoglobin, renal function and cardiovascular endpoints including blood pressure, heart/body weight ratio, serum N-terminal prohormone of brain natriuretic peptide (NT-proBNP), cardiac histology and markers of hypertrophy, fibrosis and inflammation were assessed. Results. Compared to the controls, untreated CKD group exhibited hypertension, elevated serum urea, creatinine, phosphate, and NT-proBNP concentrations, anemia, cardiomegaly ,cardiac hypertrophy and fibrosis. Treatment with ferric citrate significantly increased hemoglobin and serum iron concentrations, reduced serum phosphate and NT-proBNP levels and ameliorated hypertension, heart/body weight ratio, cardiac hypertrophy, fibrosis and inflammation. In addition, ferric citrate administration reduced the size of cardiomyocytes and expressions of myocardin, transforming growth factor-β, interleukin-6 and monocyte chemotactic protein 1. Conclusions. Treatment with ferric citrate attenuated renal failure and cardiovascular abnormalities including myocardial hypertrophy and fibrosis in CKD rats.